REALISASI ANGGARAN PENERIMAAN DAN PENGELUARAN PADA KANTOR KONI KABUPATEN KUTAI BARAT - Titin Ruliana, Henik, Elfreda A.Lau, (EKONOMIA, 2015)
In Organizational Unit  of  Committee of  National Sport which duty and its function to arrange the manajemenisasi, distribution, and activity organization  of  every sport branch still not yet effective, to improve repair the the problem  is hence needed by  an analysis expected can become the effective solution so that this sksipsi study about Realization of budget of acceptance and expenditure at  Office KONI Regency of  Kutai west of  period  2013-2014. Data type used  by  that is data of primary and method of Comparability research. Where population used  by  entire/all existing athletic branch. accurate  by  Problem formula that is Whether ,What realization of acceptance and expenditure have effective and whether,what efficient budget realization  at  athletic branch of TEKWONDO, PABBSI, PBSI, PODSI And PSSI, so that this research background that is Realization of budget of acceptance and expenditure at Office KONI Regency Kutai West, this research hypothesis as follows Realize the Acceptance and Expenditure have effective and Efficient Realisai Budget with the budget of acceptance and athletic branch expenditure of TAEKWONDO, PABBSI, PBSI, PODSI And PSSI  at  Office  of  KONI  period 2013-2104 .  Analyzer weared by that is earnings Effectiveness and Analyse the Expenditure Efficiency.                Hence result of research obtained by that is Realization of Budget of Acceptance and Pengeluran of at  Office of KONI of Regency of Kutai West " in  accepted or have effective.